If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + -7 + 3p = 0 Reorder the terms: -7 + 5p + 3p = 0 Combine like terms: 5p + 3p = 8p -7 + 8p = 0 Solving -7 + 8p = 0 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + 8p = 0 + 7 Combine like terms: -7 + 7 = 0 0 + 8p = 0 + 7 8p = 0 + 7 Combine like terms: 0 + 7 = 7 8p = 7 Divide each side by '8'. p = 0.875 Simplifying p = 0.875
| 4/3x=-1 | | 4q^2-20q+4=0 | | (x+8)(x+8)=25 | | 14/5x=1 | | -3p-2(6-5p)=3(p-2)-14 | | (x+8)(x+8)=-25 | | (x-2)(x-2)=64 | | 12(z+1)-4(2-2)=4(z-4)+3(2-4) | | 2x^2-2+130=0 | | v^2-5v=-4 | | -14-5(x+2)=2x-6(x+3) | | 10(x+1)=0 | | 3x+7x+11=3x+25 | | 8v-24=432 | | 3x-15=6x-9y | | 13+17m-8= | | 1/5x=x-12 | | 5h+2(11-h)=15 | | 5(x-1)=65 | | 11w+12w-7+5=-3w+5-7 | | 11w+21(3w-1)=15w | | 2-1/7x=4 | | 3+12x-5=22 | | 25(4x+2)=150 | | 8x+3y-5x+7-10y+2= | | 4x-12x-12x+36=4x^2+36 | | (7j-h)(7j-h)(7j-h)= | | x^2+105=5 | | ln(2)=.69 | | 3n+5n=8 | | 1-x-6x=-6 | | X+6-3=-3 |